P42 Evaluating interprofessional simulation for pre-registration doctors: factor analysis of the hidden curriculum. (3rd November 2019) - Whittaker, Joshua; Stoney, Ben; Deutsch, Peter; O'Connor, Kate; Clarke, Sarah; Calthorpe, Nicola
Abstract : Background: The General Medical Council recognises assistantships in preparing final year medical students for their first clinical job. These placements focus on shadowing junior doctors to help develop understanding of professional norms, system workings and to practice common skills. We aimed to investigate whether simulation could have an added benefit to this placement. Summary of work: Medical students were recruited during their assistantship period at a single district general hospital. A 21-item scale was designed by consensus to measure self-rated confidence in areas of practice considered common for junior doctors. Participants completed assessments at the start of their shadowing and before and after an interprofessional simulation session at the end of the placement. Non-parametric significance testing was used to assess individual changes in confidence. Factor Analysis was employed to examine construct validity of the scale. Summary of results: 25 students completed assessments. Average pre-placement confidence ranged from 20.5% to 57.5% across the 21 items. There was a significant increase in confidence after the shadowing in 18 of 21 items (p<0.05). Simulation provided an additional significant increase in confidence in 12 of 21 items, including the 3 items not increased during the shadowing alone. The items included in this group include 'dealing with difficult relatives', 'managing acutely unwell admissions' and 'participating in a cardiac arrest call'. Factor analysis revealed that the scale lacks construct validity however it demonstrated that students consistently appear less confident dealing with on-call tasks compared to day-to-day tasks. Discussion: Simulation can provide experience useful for learning which is not necessarily provided by shadowing along. Pre-registration doctors' confidence appears to be higher in tasks felt to be day-to-day for junior doctors and less in on-call tasks. They also grouped items in a third category: dealing with difficult situations. Simulation increased the confidence in all areas and brought the item included in the latter category into alignment with day-to-day tasks. Factor analysis has a number of weaknesses but this should be considered a useful tool in the evaluation of simulation programmes of any size. Conclusions: Simulation, in addition to standard assistantship placements, can provide a further increase in confidence in tasks associated with being a junior doctor and can provide experiential learning not otherwise acquired. Recommendations: Simulation programmes should be incorporated into assistantship placements and statistical methods of evaluation should be considered when designing programme of any size.